2007
DOI: 10.1071/ea07012
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of Hereford Shorthorn cattle following challenge with Boophilus microplus tick larvae

Abstract: The ability of cattle to resist tick infestations is partly genetically determined. In order to better define the nature of Bos taurus resistance to the cattle tick Boophilus microplus, skin gene expression was studied using a cattle skin derived cDNA microarray. Expression profiles were determined in skin biopsies sampled from three highly tick resistant animals (HR) and two animals with lower tick resistance (LR) at time 0, immediately before challenge, and again 24 h after challenge. The analysis of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 43 publications
8
38
2
2
Order By: Relevance
“…MAN2A1 mutations are involved in systemic autoimmune disease (Chui et al 2001), and the expression of ABCA9 was affected by cholesterol levels in blood and it belongs to a family of genes that are induced during monocyte differentiation into macrophages (Piehler et al 2002). None of the genes listed in Table 8 was identified by gene expression profiling in cattle following artificial challenge using B. microplus larvae (Wang et al 2007).…”
Section: Gwas Results For Tick Burdenmentioning
confidence: 99%
“…MAN2A1 mutations are involved in systemic autoimmune disease (Chui et al 2001), and the expression of ABCA9 was affected by cholesterol levels in blood and it belongs to a family of genes that are induced during monocyte differentiation into macrophages (Piehler et al 2002). None of the genes listed in Table 8 was identified by gene expression profiling in cattle following artificial challenge using B. microplus larvae (Wang et al 2007).…”
Section: Gwas Results For Tick Burdenmentioning
confidence: 99%
“…Wang et al (2007) evaluated B. taurus animals and observed decreased CXCL8 expression in the skin of susceptible animals after infestation. Hajnická et al (2001) demonstrated anti-CXCL8 action in the salivary gland extract (SGE) of several tick species.…”
Section: Foxp3mentioning
confidence: 99%
“…Most of these studies were performed using skin biopsies from the infestation site (Wang et al, 2007;Kongsuwan et al, 2008;Bagnall et al, 2009;Nascimento et al, 2010;Piper et al, 2008Piper et al, , 2010, and thus far, only one study has evaluated the peripheral blood gene expression in bovine (Piper et al, 2009). The lack of available samples before the artificial infestation, however, has limited understanding of the response process to the tick.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have reported that numerous ribosomal proteins show extra-ribosomal functions, such as involvement with several human genetic disorders (Wool, 1996). Studies in gene expression profiling on cattle skin have found an enormous number of ribosomal proteins up regulated in response to a challenge with ticks in both high and low resistance animals (Wang et al, 2007). Furthermore, it is known that global changes in the expression of ribosomal proteins can occur as a response to stress (Causton et al, 2001).…”
Section: Discussionmentioning
confidence: 99%